Faktor-Faktor yang Mempengaruhi Peranan Kelompok Tani dalam Penerapan Inovasi Teknologi Budidaya Cabai di Lahan Pasir Pantai Kabupaten Kulon Progo - Muhamad Rom Ali Fikri (Program Studi Agribisnis, Fakultas Pertanian, Universitas Singaperbangsa Karawang, 2021)
The sandy beach land was one of solution to overcome rise of land conversion in agriculture sector and has important potential in horticultural dvelopment including of chili commodities. In the adoption of chili cultivation technology in coastal sandy land need support of farmer group since the innovation of agroinput, agroproduct, agroprocessing and agromarketing. The role of farmer group determining the success of agriculture innovation development. The goals were; to know the factors affecting the role of farmer group in adoption of chili cultivation technology in coastal sandy land. The basic method used in this research was analytical descriptive with survey technique. The research was conducted in Bugel Village, Panjatan Sub-District, Kulon Progo Regency and The village sample was selected purposively, that was Bugel Village. Each village sample was selected purposively as much as two farmer group samples which had most potential in adoption of chili cultivation technology in coastal sandy land. “Gisik Pranaji” and “Gisik Wanatara” From both groups using simple random sampling with forty farmers as respondents. Data were analyzed by frequency distribution tables and multiple linear regression analysis. The results showed that farmer groups always have a role in adoption of chili cultivation technology in coastal sandy land, Kulon Progo Regency. The role of farmer groups were influenced positively by leader role of farmer groups, while the liveliness of farmer group member and the role of agricultural extension workers had no effect in the role of farmer groups. Key words: Role, Farmer Group, technology adoption, chili, and coastal sandy land.